Ruthenium-doped bimetallic phosphide catalysts, methods of making, and use in electrocatalytic selective oxidation of alcohols to assist hydrogen production

CN117488351BActive Publication Date: 2026-10-16CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311451406.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-02
Publication Date
2026-10-16
Estimated Expiration
2043-11-02

AI Technical Summary

Technical Problem

[0004]迄今为止,许多贵金属基催化剂在强碱电解质中苯甲醇氧化反应(Benzylalcohol Oxidation Reaction,BOR)的研究上表现出优异的性能,但是贵金属材料的成本高,达到EAO的工业要求仍有一定差距,应用范围受限

Benefits of technology

[0027]This invention provides a method for preparing a ruthenium-doped bimetallic phosphide catalyst, comprising the following steps: S1) mixing and dispersing cobalt salt, metal M salt, urea, ammonium fluoride, and water to obtain a precursor solution; wherein the metal M salt is selected from one or more of nickel salt, cobalt salt, and copper salt; S2) mixing a conductive support with the precursor solution and heating to perform a hydrothermal reaction to obtain a bimetallic precursor material; S3) impregnating the bimetallic precursor material in a ruthenium salt alcohol solution, then removing and drying it to obtain a ruthenium-doped bimetallic precursor material; wherein the ruthenium salt alcohol solution comprises a ruthenium salt and an alcohol solvent; S4) phosphating the ruthenium-doped bimetallic precursor material in a protective atmosphere to obtain a ruthenium-doped bimetallic phosphide catalyst. Compared with existing technologies, this invention synthesizes a highly efficient and stable ruthenium-doped bimetallic phosphide catalyst through a simple hydrothermal and phosphating method. This catalyst is used for the electrocatalytic oxidation of alcohols to assist hydrogen evolution. It possesses a nanoarray structure, and the rough nanosheet surface provides a high specific surface area, which is beneficial for charge transfer and significantly improves catalytic activity. Furthermore, the catalyst exhibits good cycling stability. In the selective electrocatalytic oxidation of alcohols, it facilitates the diffusion and transport of the alcohol reaction substrate, resulting in high reaction conversion and selectivity. Moreover, the catalyst has a simple preparation process and abundant active sites, providing a new approach for the green and efficient selective electrocatalytic oxidation of alcohol molecules to assist hydrogen evolution, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004529928550000011
    Figure HDA0004529928550000011
  • Figure HDA0004529928550000012
    Figure HDA0004529928550000012
  • Figure HDA0004529928550000021
    Figure HDA0004529928550000021
Patent Text Reader

Abstract

The application provides a preparation method of a ruthenium-doped bimetallic phosphide catalyst. Compared with the prior art, the ruthenium-doped bimetallic phosphide catalyst is synthesized by a simple hydrothermal and phosphorization method, is used for alcohol electrocatalytic oxidation assisted hydrogen evolution, has a nano array structure, a rough nanosheet surface provides a high specific surface area, is favorable to charge transfer, can obviously improve catalytic activity, and has good cycle stability; in the selective electrocatalytic oxidation reaction of alcohol, the catalyst is favorable to diffusion and transmission of alcohol reaction substrates, has high reaction conversion rate and selectivity, the catalyst preparation process is simple, active sites are rich, a new idea is provided for green and efficient selective electrocatalytic oxidation of alcohol molecules assisted hydrogen evolution, and the catalyst has wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic electrochemical technology, and particularly relates to a ruthenium-doped bimetallic phosphide catalyst, its preparation method, and its application in electrocatalytic selective oxidation of alcohols to assist hydrogen production. Background Technology

[0002] Industrial and economic development has driven rapid social progress, but human dependence on and consumption of fossil fuels such as coal and oil have led to problems such as the greenhouse effect and environmental pollution. Therefore, finding renewable resources is crucial to reducing dependence on petroleum energy and CO2 emissions. Hydrogen (H2) has become a suitable energy carrier and clean fuel due to its high energy density and environmental friendliness. Among these technologies, electrochemical water splitting for hydrogen production has become a focus of competition as a green and promising key technology. However, the slow kinetics of its oxygen evolution reaction (OER) at the anode and the high cost due to high energy consumption have constrained its development. In addition, the commercial value of oxygen (O2) produced in the OER process is very limited in practical applications. Therefore, new strategies are needed to overcome these challenges and achieve efficient hydrogen production at low potentials, fundamentally solving the energy consumption problem required for electrocatalytic hydrogen production.

[0003] In recent years, chemically assisted electrocatalytic hydrogen evolution (EAO) has been widely used as a novel water electrolysis method. Its strategy involves using the oxidation reaction of reducing chemicals to replace the anodic oxidation (OER) process. This anodic oxidation reaction can produce value-added products from inexpensive industrial raw materials or renewable biomass resources, effectively reducing the overpotential of the anodic reaction, and the resulting high-value-added products bring greater economic benefits. Simultaneously, this process can prevent the formation of explosive H2 and O2 mixtures caused by gas cross-contamination, offering numerous safety and energy advantages. Therefore, EAO is considered an important strategy for improving hydrogen production efficiency and producing high-value-added chemicals, bringing water electrolysis to a new level. In this regard, hybrid water electrolysis systems integrating electrocatalytic alcohol oxidation (EAO) and hydrogen evolution reaction (HER) have been rapidly developed. The theoretical potential (0.48V) of the electrocatalytic oxidation of benzyl alcohol is lower than that of the OER reaction in water electrolysis, making it more favorable for hydrogen production while reducing energy consumption. Furthermore, compared to the energy-intensive toluene oxidation process in industry, the electrocatalytic oxidation of benzyl alcohol is milder and greener. Therefore, replacing the traditional oxygen evolution reaction with the electrocatalytic oxidation of inexpensive benzyl alcohol at the anode is a promising strategy to promote hydrogen production, minimize energy consumption, and achieve green synthesis of benzoic acid.

[0004] To date, many noble metal-based catalysts have demonstrated excellent performance in the benzyl alcohol oxidation reaction (BOR) in strong alkaline electrolytes. However, the high cost of noble metal materials and their failure to meet the industrial requirements of electrocatalytic hydrogen evolution (EAO) limit their application. Therefore, there is an urgent need to develop non-noble metal catalyst materials and improve their application in electrocatalytic assisted hydrogen evolution by optimizing their geometry and electronic structure. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a ruthenium-doped bimetallic phosphide catalyst with good selective electrocatalytic oxidation performance of alcohols, its preparation method, and its application in assisted hydrogen production by selective electrocatalytic oxidation of alcohols.

[0006] This invention provides a method for preparing a ruthenium-doped bimetallic phosphide catalyst, comprising the following steps:

[0007] S1) Cobalt salt, metal M salt, urea, ammonium fluoride and water are mixed and dispersed to obtain a precursor solution; the metal M salt is selected from one or more of nickel salt, cobalt salt and copper salt;

[0008] S2) The conductive carrier is mixed with the precursor solution and heated to carry out a hydrothermal reaction to obtain a bimetallic precursor material;

[0009] S3) The bimetallic precursor material is immersed in a ruthenium salt alcohol solution, then removed and dried to obtain a ruthenium-doped bimetallic precursor material; the ruthenium salt alcohol solution includes a ruthenium salt and an alcohol solvent.

[0010] S4) In a protective atmosphere, the ruthenium-doped bimetallic precursor material is phosphated to obtain a ruthenium-doped bimetallic phosphide catalyst.

[0011] Preferably, the cobalt salt is selected from cobalt chloride and / or cobalt nitrate;

[0012] The metal M salt is selected from the chloride salt of metal M and / or the nitrate salt of metal M;

[0013] The molar ratio of the cobalt salt to the metallic M salt is (0.5-2):(0.5-1).

[0014] Preferably, the molar ratio of the cobalt salt to urea is (0.5-2):(5-10);

[0015] The molar ratio of urea to ammonium fluoride is (5-10):(1-5).

[0016] Preferably, the temperature of the hydrothermal reaction is 90℃~180℃; and the time of the hydrothermal reaction is 1.5~3h.

[0017] Preferably, the concentration of ruthenium salt in the ruthenium salt alcohol solution is 0.01–1 g / mL; and the immersion time is 30–90 min.

[0018] Preferably, the phosphating temperature is 300℃~500℃; the phosphating time is 1~3h.

[0019] The present invention also provides a ruthenium-doped bimetallic phosphide catalyst, comprising a conductive support and a ruthenium-doped bimetallic phosphide supported on the conductive support; the ruthenium-doped bimetallic phosphide is a nanosheet structure; the nanosheet structure is vertically staggered on the conductive support to form a nanoarray structure.

[0020] Preferably, the thickness of the nanosheet structure is 20–25 nm.

[0021] This invention also provides the application of the above-mentioned ruthenium-doped bimetallic phosphide catalyst in electrocatalytic selective oxidation of alcohols to assist hydrogen production.

[0022] Preferably, the ruthenium-doped bimetallic phosphide catalyst is an anode catalyst;

[0023] The alcohols are selected from one or more of methanol, ethanol, benzyl alcohol, and glycerol;

[0024] The concentration of alcohols in the electrolyte solution for selective oxidation of alcohols to assist hydrogen production is greater than or equal to 10 mmol / L.

[0025] The electrolyte solution for selective oxidation of alcohols to assist hydrogen production is an aqueous solution of alkali metal hydroxide; the pH value of the electrolyte solution is 10-14.

[0026] The voltage for selective oxidation of alcohols to assist in hydrogen production is 1–2 V.

[0027] This invention provides a method for preparing a ruthenium-doped bimetallic phosphide catalyst, comprising the following steps: S1) mixing and dispersing cobalt salt, metal M salt, urea, ammonium fluoride, and water to obtain a precursor solution; wherein the metal M salt is selected from one or more of nickel salt, cobalt salt, and copper salt; S2) mixing a conductive support with the precursor solution and heating to perform a hydrothermal reaction to obtain a bimetallic precursor material; S3) impregnating the bimetallic precursor material in a ruthenium salt alcohol solution, then removing and drying it to obtain a ruthenium-doped bimetallic precursor material; wherein the ruthenium salt alcohol solution comprises a ruthenium salt and an alcohol solvent; S4) phosphating the ruthenium-doped bimetallic precursor material in a protective atmosphere to obtain a ruthenium-doped bimetallic phosphide catalyst. Compared with existing technologies, this invention synthesizes a highly efficient and stable ruthenium-doped bimetallic phosphide catalyst through a simple hydrothermal and phosphating method. This catalyst is used for the electrocatalytic oxidation of alcohols to assist hydrogen evolution. It possesses a nanoarray structure, and the rough nanosheet surface provides a high specific surface area, which is beneficial for charge transfer and significantly improves catalytic activity. Furthermore, the catalyst exhibits good cycling stability. In the selective electrocatalytic oxidation of alcohols, it facilitates the diffusion and transport of the alcohol reaction substrate, resulting in high reaction conversion and selectivity. Moreover, the catalyst has a simple preparation process and abundant active sites, providing a new approach for the green and efficient selective electrocatalytic oxidation of alcohol molecules to assist hydrogen evolution, and has broad application prospects. Attached Figure Description

[0028] Figure 1 The X-ray diffraction pattern of the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 of this invention;

[0029] Figure 2 This is a scanning electron microscope image of the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 of the present invention;

[0030] Figure 3 The XPS spectrum of the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 of this invention is shown below.

[0031] Figure 4 The polarization curve of the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 of the present invention is shown at a scan rate of 5 mV / s.

[0032] Figure 5 The polarization curves of the ruthenium-doped bimetallic phosphide catalyst and the control sample obtained in Example 1 of this invention in 1M KOH + 20mM benzyl alcohol are shown.

[0033] Figure 6 The liquid chromatogram of the product obtained after catalysis by the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 of this invention;

[0034] Figure 7The conversion rate, selectivity, and Faraday efficiency of the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 of this invention are shown in the diagram.

[0035] Figure 8 This is a stability test diagram of the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 of the present invention;

[0036] Figure 9 The image shows the polarization curve of the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 of this invention as a bifunctional catalyst in a two-electrode system. Detailed Implementation

[0037] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0038] This invention provides a method for preparing a ruthenium-doped bimetallic phosphide catalyst, comprising the following steps: S1) mixing and dispersing cobalt salt, metal M salt, urea, ammonium fluoride, and water to obtain a precursor solution; wherein the metal M salt is selected from one or more of nickel salt, cobalt salt, and copper salt; S2) mixing a conductive support with the precursor solution and heating to perform a hydrothermal reaction to obtain a bimetallic precursor material; S3) impregnating the bimetallic precursor material in a ruthenium salt alcohol solution, then removing and drying it to obtain a ruthenium-doped bimetallic precursor material; wherein the ruthenium salt alcohol solution comprises a ruthenium salt and an alcohol solvent; S4) phosphating the ruthenium-doped bimetallic precursor material in a protective atmosphere to obtain a ruthenium-doped bimetallic phosphide catalyst.

[0039] In this invention, there are no special restrictions on the source of any raw materials; they can be commercially available.

[0040] A precursor solution is obtained by mixing and dispersing cobalt salt, metal M salt, urea, ammonium fluoride, and water. The cobalt salt can be any cobalt salt known to those skilled in the art and is not particularly limited; in this invention, cobalt chloride and / or cobalt nitrate are preferred. The metal M salt is one or more of nickel, cobalt, and copper salts. The metal M salt is preferably a chloride of metal M and / or a nitrate of metal M. The molar ratio of cobalt salt to metal M salt is preferably (0.5–2):(0.5–1), more preferably (0.5–1.5):(0.5–1), even more preferably (0.8–1.2):(0.8–1), and most preferably 1:1. The molar ratio of cobalt salt to urea is preferably (0.5–2):(5–10), more preferably (0.5–1.5):(5–10). The molar ratio of urea to ammonium fluoride is preferably (5-10):(1-5), more preferably (6-9):(2-4), more preferably (7-9):(2.5-3.5), and most preferably 8:3; the water is preferably distilled water; the mixing and dispersion method is preferably ultrasonic dispersion; the mixing and dispersion time is preferably 30-60 min; the concentration of cobalt salt in the precursor solution is preferably 0.01-0.1 mol / L, more preferably 0.01-0.06 mol / L, more preferably 0.02-0.05 mol / L, and most preferably 0.025-0.03 mol / L.

[0041] A hydrothermal reaction is carried out by mixing a conductive carrier with a precursor solution and heating the mixture to obtain a bimetallic precursor material. The conductive carrier can be any conductive carrier well-known to those skilled in the art and is not particularly limited; in this invention, carbon cloth or nickel foam is preferred. The unit weight of the carbon cloth is preferably 110–180 g / cm³. 2The thickness of the carbon cloth is preferably 0.1–0.5 mm, more preferably 0.3–0.4 mm, and even more preferably 0.34–0.38 mm. In this invention, the conductive carrier is preferably pretreated before being mixed with the precursor solution. The pretreatment preferably specifically involves: ultrasonically washing the conductive carrier sequentially in acetone, anhydrous ethanol, deionized water, and nitric acid aqueous solution to remove impurities from the surface of the conductive carrier; finally, the conductive carrier is removed and rinsed with deionized water to remove the nitric acid, and then dried. The ultrasonic washing time for each step is independently 10–60 min. The hydrothermal reaction… The preferred temperature is 90℃~180℃, more preferably 90℃~150℃, even more preferably 110℃~150℃, and most preferably 120℃; the preferred hydrothermal reaction time is 1.5~3h, more preferably 2~3h, and even more preferably 2.5h; after the hydrothermal reaction, it is preferred to cool to room temperature, and the product is taken out, washed, and dried to obtain the bimetallic precursor material; the washing is preferably done with distilled water and ethanol; the drying is preferably vacuum drying; the preferred temperature for vacuum drying is 50℃~80℃, more preferably 50℃~60℃; and the preferred time for vacuum drying is 10~24h.

[0042] A bimetallic precursor material is immersed in a ruthenium salt alcohol solution, then removed and dried to obtain a ruthenium-doped bimetallic precursor material. The ruthenium salt alcohol solution comprises a ruthenium salt and an alcohol solvent. The ruthenium salt can be any ruthenium salt known to those skilled in the art and is not particularly limited; in this invention, ruthenium chloride and / or ruthenium nitrate are preferred. The alcohol solvent is preferably methanol and / or ethanol, more preferably ethanol. The concentration of the ruthenium salt in the ruthenium salt alcohol solution is preferably 0.01–1 g / mL, more preferably 0.05–0.5 g / mL. The concentration of ruthenium salt in alcohol is preferably 0.05–0.2 g / mL, and most preferably 0.1 g / mL; the ruthenium salt alcohol solution is preferably obtained by ultrasonically dispersing a mixture of ruthenium salt and alcohol solvent; the ultrasonic dispersion time is preferably 30–60 min; the impregnation time is preferably 30–90 min; the drying is preferably vacuum drying; the vacuum drying temperature is preferably 50°C–80°C, more preferably 50°C–60°C; the vacuum drying time is preferably 10–24 h.

[0043] In a protective atmosphere, the ruthenium-doped bimetallic precursor material is phosphated to obtain a ruthenium-doped bimetallic phosphide catalyst. The protective atmosphere can be any atmosphere known to those skilled in the art and is not particularly limited; nitrogen is preferred in this invention. The phosphorus source used for phosphating can be any phosphorus source known to those skilled in the art and is not particularly limited; hypophosphite and / or elemental phosphorus are preferred in this invention, more preferably hypophosphite, and even more preferably sodium hypophosphite. The ratio of the conductive support to the phosphorus source is preferably 1 cm⁻¹. 2 (0.1~0.2)g, more preferably 1cm 2(0.1~0.15)g, preferably 1cm 2 (0.125~0.15)g; the phosphating is preferably carried out in a tubular reactor; the phosphorus source is preferably placed upstream of the tubular reactor; the phosphating temperature is preferably 300℃~500℃, more preferably 300℃~450℃, and even more preferably 350℃~400℃; the phosphating time is preferably 1~3h, more preferably 1.5~2.5h, and even more preferably 2h.

[0044] This invention synthesizes a highly efficient and stable ruthenium-doped bimetallic phosphide catalyst via a simple hydrothermal and phosphating method. This catalyst is used for the electrocatalytic oxidation of alcohols to assist hydrogen evolution. It possesses a nanoarray structure, and the rough nanosheet surface provides a high specific surface area, which is beneficial for charge transfer and significantly improves catalytic activity. Furthermore, the catalyst exhibits good cycling stability. In the selective electrocatalytic oxidation of alcohols, it facilitates the diffusion and transport of the alcohol reaction substrate, resulting in high reaction conversion and selectivity. Moreover, the catalyst has a simple preparation process and abundant active sites, providing a new approach for the green and efficient selective electrocatalytic oxidation of alcohol molecules to assist hydrogen evolution, and has broad application prospects.

[0045] The present invention also provides a ruthenium-doped bimetallic phosphide catalyst prepared by the above method, comprising a conductive support and a ruthenium-doped bimetallic phosphide supported on the conductive support; the ruthenium-doped bimetallic phosphide is a nanosheet structure; the nanosheet structure is vertically staggered on the conductive support to form a nanoarray structure.

[0046] More specifically, the thickness of the nanosheet structure is preferably 20–25 nm.

[0047] More specifically, the nanosheet structures are vertically interlaced and connected on a conductive carrier to form a three-dimensional network structure.

[0048] The present invention also provides the application of the above-mentioned ruthenium-doped bimetallic phosphide catalyst in electrocatalytic selective oxidation of alcohols to assist hydrogen production.

[0049] According to the present invention, the ruthenium-doped bimetallic phosphide catalyst is preferably an anode catalyst.

[0050] According to the present invention, the electrocatalytic selective oxidation of alcohols to assist hydrogen production preferably adopts a three-electrode system; in the three-electrode system, the electrode is preferably a platinum electrode and the reference electrode is Ag / AgCl.

[0051] According to the present invention, the selective oxidation of alcohols to produce hydrogen is preferably carried out using an H-type electrolyzer.

[0052] According to the present invention, the alcohols used in the electrocatalytic selective oxidation of alcohols to assist hydrogen production can be alcohol compounds well known to those skilled in the art, and there are no special restrictions. In the present invention, one or more of methanol, ethanol, benzyl alcohol and glycerol are preferred. The concentration of alcohols in the electrolyte solution in the electrocatalytic selective oxidation of alcohols to assist hydrogen production is preferably greater than or equal to 10 mmol / L. In some embodiments provided by the present invention, the concentration of alcohols in the electrolyte solution is specifically 20 mmol / L.

[0053] According to the present invention, the electrolyte solution for selective oxidation of alcohols to assist hydrogen production is preferably an aqueous solution of alkali metal hydroxide, more preferably an aqueous solution of potassium hydroxide or sodium hydroxide; the pH value of the electrolyte solution is 10-14; in some embodiments provided by the present invention, the concentration of the aqueous solution of alkali metal hydroxide is specifically 1 mol / L.

[0054] According to the present invention, the voltage for selective oxidation of alcohols to assist hydrogen production is preferably 1 to 2V; the selective oxidation of alcohols to assist hydrogen production is preferably carried out under constant current conditions; and the time for selective oxidation of alcohols to assist hydrogen production is preferably 0.5 to 10 hours.

[0055] According to the present invention, the electrocatalytic selective oxidation of alcohols to assist hydrogen production can yield high-value-added acid chemicals; the high-value-added acid chemicals are preferably one or more of the acids obtained from alcohol oxidation and their corresponding sodium and potassium salts, more preferably formic acid, acetic acid, benzoic acid, glyceric acid, and one or more of their corresponding sodium and potassium salts.

[0056] To further illustrate the present invention, the following detailed description, in conjunction with embodiments, provides a ruthenium-doped bimetallic phosphide catalyst, its preparation method, and its application in electrocatalytic selective oxidation of alcohols to assist hydrogen production.

[0057] All reagents used in the following examples are commercially available; the carbon cloth used in the examples is model HCP330N.

[0058] Example 1

[0059] 1.1 The 2×2cm carbon cloth was ultrasonically washed for 30 minutes in acetone, anhydrous ethanol, deionized water and nitric acid aqueous solution respectively to remove impurities on the surface of the carbon cloth and obtain the pretreated carbon cloth.

[0060] 1.2 The pretreated carbon cloth obtained in 1.1 was placed in a mixed solution containing 1 mmol cobalt nitrate, 1 mmol nickel nitrate, 8 mmol urea, 110 mg ammonium fluoride and 40 mL water, and transferred to a hydrothermal reactor lined with Teflon. It was heated in an oven at 120 °C for 2.5 hours. The carbon cloth substrate was removed from the hydrothermal reactor and washed with distilled water and ethanol. It was then vacuum dried at 60 °C for 10 hours to obtain the hydrothermally treated precursor.

[0061] 1.3 The hydrothermally heated precursor was immersed in an ethanol solution of RuCl3·3H2O (0.01 g RuCl3·3H2O was mixed with 10 mL of ethanol) for 2 h, and then vacuum dried at 60 °C for 10 h to obtain ruthenium-doped bimetallic precursor material.

[0062] 1.4 The ruthenium-doped bimetallic precursor material was phosphated in a tube furnace using 0.5 g NaH2PO2·H2O powder as the phosphorus source. The temperature was maintained at 350 °C for 2 h under a nitrogen atmosphere to obtain the ruthenium-doped bimetallic phosphide catalyst, denoted as Ru-NiCoP@CC.

[0063] Preparation of control samples:

[0064] The hydrothermal precursor from Example 1 was annealed in air at 350°C for 2 hours to obtain the NiCo2O4@CC sample.

[0065] NiO@CC and CO3O4@CC nanomaterials were prepared using the same steps as described above, except that no cobalt or nickel source was added during the hydrothermal reaction.

[0066] The NiCo2O4@CC sample was immersed in an ethanol solution containing RuCl3·3H2O (0.01g RuCl3·3H2O was mixed with 10mL ethanol) for 2h, and then annealed at 350℃ for 2h to obtain Ru-NiCo2O4@CC.

[0067] Crystal structure analysis of the sample

[0068] The ruthenium-doped bimetallic phosphide catalyst and control material obtained in Example 1 were scanned using a Shimadzu X-ray powder diffractometer (XRD-6100). The specific operation procedure and equipment parameters are as follows: The prepared ruthenium-doped bimetallic phosphide catalyst was cut into a small piece, adhered to the test tray with conductive adhesive, and placed in the XRD sample stage for XRD pattern scanning. The scanning parameters were as follows: the scanning range was set to 5°–90°, the scanning speed and scanning step size were 5° / min and 0.01°, respectively. Figure 1 As shown, the main peak in the XRD pattern points to Co2P4O. 12(PDF#86-2161), and simultaneously, due to the abundant presence of metal M, the XRD characteristic peaks of ruthenium-doped bimetallic phosphide electrode materials are relatively higher than those of Co2P4O. 12 There is a slight rightward shift. This indicates successful Ru and P doping, resulting in this transition metal heterostructure nanosheet supported on a three-dimensional carbon cloth substrate.

[0069] Characterization of sample morphology

[0070] The sample was prepared using a Hitachi SU8010 scanning electron microscope as follows: The ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 was cut and adhered to conductive adhesive on a copper plate. The plate was placed on a mounting stage, and its morphology was observed after adjusting the parameters. The resulting scanning electron microscope image is shown below. Figure 2 As shown. By Figure 2 It is known that ruthenium-doped bimetallic phosphides exhibit a uniform three-dimensional nanosheet structure with a relatively rough surface and almost no aggregation. The average thickness is 20-25 nm. The nanosheets are connected and vertically arranged to construct a three-dimensional network structure. The rough surface of the sheets makes the active sites more open, ensuring the effective diffusion of ions and electrons at the interface, increasing the active surface area for electrochemical reactions, and thus exhibiting better electrocatalytic activity.

[0071] X-ray photoelectron spectroscopy (XPS) of the sample

[0072] XPS spectra of the samples were measured using Thermo Fisher Scientific's Nexsa instrument, with a base vacuum of 3 × 10⁻⁶. -9 mbar, power 300W. During data processing, the C1s peak of contaminated carbon is used to perform energy correction on XPS. Then, by comparing with standard spectra and using XPSPEAK software to perform peak fitting on the full spectrum of XPS and high-resolution spectra of major metal elements, the valence states and bonding relationships between elements are preliminarily determined, resulting in the XPS energy spectrum of the ruthenium-doped bimetallic phosphide catalyst, such as... Figure 3 As shown. By Figure 3 It can be seen that the surface of the ruthenium-doped bimetallic phosphide sample is mainly composed of Ru, Co, M, P and O elements. At the same time, the shift of the position of each peak indicates that the doping of P element can effectively regulate the chemical environment of the metal site and may have a positive impact on the catalytic ability. The doping of Ru is conducive to accelerating electron transfer and optimizing proton adsorption.

[0073] Polarization curves of electrode materials

[0074] The ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 was used as the working electrode. An Ag / AgCl electrode and a Pt sheet were used as the reference and counter electrodes, respectively. 1M potassium hydroxide solution and 20mM benzyl alcohol (BA) were used as the electrolyte and electrolyte, respectively, with comparisons made to a solution without 20mM BA. Electrochemical tests were performed on a Shanghai Chenhua 760E electrochemical workstation at a scan rate of 5mV / s. Figure 4 As shown, ruthenium-doped bimetallic phosphides only require 1.316V (corresponding to 10mA cm⁻¹) to achieve the corresponding current density. -2 ) and 1.411V (corresponding to 100mA cm -2 The low potential of Ru significantly reduces the anolyte potential in benzyl alcohol solution, indicating that benzyl alcohol is oxidized at the electrode much more readily than by water. This suggests that Ru single atoms play a crucial role in BOR, facilitating the exposure of catalytic active sites and promoting charge transfer during the reaction, thus improving catalytic kinetics. Furthermore, the synergistic effect of nickel and cobalt further enhances the current density. Thanks to the doping of Ru and P, the coordination effect between bimetallic phosphides, and the unique three-dimensional interconnected nanosheet structure, Ru exhibits outstanding constitutive activity and abundant accessible active sites, thereby driving the kinetics of the BOR process more easily.

[0075] The ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 and the control sample were used as working electrodes, respectively. Then, an Ag / AgCl electrode and a Pt sheet were used as the reference electrode and counter electrode, respectively. 1M potassium hydroxide solution and 20mM benzyl alcohol (BA) were used as the electrolyte and electrolyte, respectively. Electrochemical tests were performed on a Shanghai Chenhua 760E electrochemical workstation at a scan rate of 5mV / s. The polarization curves of CO3O4@CC, NiO@CC, NiCo2O4@CC, Ru-NiCo2O4@CC, and Ru-NiCoP@CC in 1M KOH + 20mM benzyl alcohol are shown below. Figure 5 As shown. By Figure 5 It can be seen that the performance of several types of catalysts for electrocatalytic benzyl alcohol varies significantly. Ru-NiCoP@CC only requires 1.316V (corresponding to 10mA cm⁻¹) to achieve the corresponding current density. -2 ) and 1.411V (corresponding to 100mA cm -2 The low potential of CO3O4@CC, NiO@CC, NiCo2O4@CC, and Ru-NiCo2O4@CC for BA oxidation requires 1.426V, 1.393V, 1.370V, and 1.352V (relative to RHE) to reach 10mA cm⁻¹, respectively. -2It is evident that Ru-NiCoP@CC exhibits superior electrocatalytic performance compared to other control catalysts. This indicates that the formation of heterostructures on the carbon cloth substrate facilitates the creation of additional active sites, and the three-dimensional interconnected nanosheet structure significantly increases the number of available active sites. The binary metal composite plays a crucial role in regulating the lattice oxygen ligand environment, enhancing the adsorption capacity of reactive oxygen species. The formation of catalytically active CoNiOOH during the electrocatalytic process in Ru-NiCoP@CC leads to enhanced performance in organic oxidation reactions. Furthermore, the doping of Ru and P, the coordination effect between the bimetallic phosphides, and the unique three-dimensional interconnected nanosheet structure contribute to its outstanding constitutive activity and abundant accessible active sites, thereby facilitating the kinetics of the BOR process.

[0076] Liquid chromatogram of electrode materials

[0077] The Ru-NiCoP@CC catalyst obtained in Example 1 was used to catalyze a 1M potassium hydroxide solution containing 20mM benzyl alcohol, and the resulting product was characterized by liquid chromatography. The liquid chromatograms of the products at different reaction times are shown below. Figure 6 As shown. Figure 6 Three peaks were observed, clearly showing a continuous increase in benzoic acid (Ph-COOH) and a decrease in benzyl alcohol. This indicates that benzyl alcohol can be converted to benzoic acid via electrocatalytic oxidation on a ruthenium-doped bimetallic phosphide electrode material, exhibiting high selectivity for benzoic acid.

[0078] Conversion rate, selectivity and Faraday efficiency of electrode materials

[0079] Electrochemical performance testing and data acquisition were conducted using a Nafion 117 membrane-separated two-compartment H-type electrolytic cell. An Ag / AgCl (3MKCl) electrode was used as the reference electrode, a platinum sheet as the counter electrode, and the ruthenium-doped bimetallic phosphide catalyst obtained in Example 1 as the working electrode. A 1M potassium hydroxide solution containing 20mM benzyl alcohol was used as the electrolyte, with a potential range of 1.3V–1.5V. Conversion, selectivity, and Faraday efficiency plots of the ruthenium-doped bimetallic phosphide catalyst were obtained, as shown below. Figure 7 As shown. By Figure 7 It was found that the conversion rate, Ph-COOH selectivity, and Faradaic efficiency during the BA electrolysis process all exhibited excellent benzoic acid conversion and selectivity with no significant differences at different potentials. Simultaneously, a high Faradaic efficiency was observed at low potentials. These results indicate that ruthenium-doped bimetallic phosphides possess excellent performance for BOR, surpassing most reported benzyl alcohol and other alternative non-noble metal electrocatalysts for anodic oxidation. This suggests that the unique heterostructure formed leads to its superior electrocatalytic performance for BA oxidation through this interfacial synergistic effect.

[0080] Stability of electrode materials

[0081] The stability of BA oxidation was evaluated through repeated iterative current (IT) tests. The experiment was terminated after 4800 s of constant current testing, and was repeated 7 times. The long-term stability of the ruthenium-doped bimetallic phosphide sample was verified in a 1M potassium hydroxide solution containing 20 mM benzyl alcohol. The stability test results are shown in the figure below. Figure 8 As shown. By Figure 8 It can be seen that after 7 cycles, the LSV curve of this electrode material changes almost negligibly, indicating that it has good catalytic stability and excellent BA oxidation performance.

[0082] Electrode materials as bifunctional catalysts

[0083] Using the ruthenium-doped bimetallic phosphide obtained in Example 1 as the anode and cathode electrocatalysts, and an Ag / AgCl electrode as the reference electrode, a BA oxidation-coupled two-electrode electrolyzer was constructed with 1M KOH and 20mM BA as the electrolyte solution. For comparison, pure water splitting was also measured in a 1M KOH solution without 20mM BA. The measurements were performed on a Shanghai Chenhua 760E electrochemical workstation at a scan rate of 5mV / s. The polarization curves of the ruthenium-doped bimetallic phosphide electrode material as a bifunctional catalyst in the two-electrode system are shown below. Figure 9 As shown. By Figure 9 It can be seen that the assembled dual-electrode electrolyzer, under the condition of 1mKOH without 20mMBA solution, at 10mA cm⁻¹ -2 Under ideal conditions, the applied potential exhibits a high operating potential of 1.76 V (vs. RHE). Conversely, in the presence of 20 mM BA, the applied potential decreases significantly to 1.53 V (vs. RHE), which is favorable for HER. This coupling method will facilitate renewable energy-driven electrocatalytic HER to H2 production while simultaneously obtaining value-added chemicals.

[0084] In summary, this invention presents a novel sheet-like nanoarray of ruthenium-doped bimetallic phosphide supported in situ on carbon cloth, serving as a highly active and stable electrocatalyst for selective oxidation of alcohols to assist in hydrogen evolution. This catalyst facilitates renewable energy-driven electrocatalytic hydrogen evolution reactions, significantly reducing hydrogen production energy consumption and increasing the hydrogen production rate, while simultaneously catalyzing the directed oxidation of alcohols to obtain high-value-added chemicals such as acids. This invention provides a new strategy for designing efficient, low-cost organic small-molecule electrocatalysts to promote green hydrogen production, and also offers a novel approach for efficient freestanding electrodes for assisted hydrogen evolution reactions involving organic oxidation.

[0085] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a ruthenium-doped bimetallic phosphide catalyst, characterized in that, Includes the following steps: S1) Cobalt salt, metal M salt, urea, ammonium fluoride and water are mixed and dispersed to obtain a precursor solution; The metal M salt is selected from nickel salts; S2) The conductive carrier is mixed with the precursor solution and heated to carry out a hydrothermal reaction to obtain a bimetallic precursor material; S3) The bimetallic precursor material is immersed in a ruthenium salt alcohol solution, then removed and dried to obtain a ruthenium-doped bimetallic precursor material; the ruthenium salt alcohol solution includes a ruthenium salt and an alcohol solvent; S4) In a protective atmosphere, the ruthenium-doped bimetallic precursor material is phosphated to obtain a ruthenium-doped bimetallic phosphide catalyst.

2. The preparation method according to claim 1, characterized in that, The cobalt salt is selected from cobalt chloride and / or cobalt nitrate; The metal M salt is selected from the chloride salt of metal M and / or the nitrate salt of metal M; The molar ratio of the cobalt salt to the metallic M salt is (0.5~2):(0.5~1).

3. The preparation method according to claim 1, characterized in that, The molar ratio of the cobalt salt to urea is (0.5~2):(5~10). The molar ratio of urea to ammonium fluoride is (5~10):(1~5).

4. The preparation method according to claim 1, characterized in that, The hydrothermal reaction temperature is 90℃~180℃; the hydrothermal reaction time is 1.5~3 h.

5. The preparation method according to claim 1, characterized in that, The concentration of ruthenium salt in the ruthenium salt alcohol solution is 0.01~1 g / mL; the immersion time is 30~90 min.

6. The preparation method according to claim 1, characterized in that, The phosphating temperature is 300℃~500℃; the phosphating time is 1~3 h.

7. A ruthenium-doped bimetallic phosphide catalyst prepared by any one of claims 1 to 6, characterized in that, It includes a conductive carrier and a ruthenium-doped bimetallic phosphide loaded on the conductive carrier; the ruthenium-doped bimetallic phosphide is a nanosheet structure; the nanosheet structure is vertically staggered on the conductive carrier to form a nanoarray structure.

8. The ruthenium-doped bimetallic phosphide catalyst according to claim 7, characterized in that, The thickness of the nanosheet structure is 20~25 nm.

9. The application of the ruthenium-doped bimetallic phosphide catalyst prepared by any one of claims 1 to 6 or the ruthenium-doped bimetallic phosphide catalyst according to claim 7 or 8 in the selective oxidation of benzyl alcohol to assist hydrogen production via electrocatalysis.

10. The application according to claim 9, characterized in that, The ruthenium-doped bimetallic phosphide catalyst is an anode catalyst; The concentration of benzyl alcohol in the electrolyte solution for selective oxidation of benzyl alcohol to hydrogen production via electrocatalysis is greater than or equal to 10 mmol / L. The electrolyte solution for selective oxidation of benzyl alcohol to produce hydrogen via electrocatalysis is an aqueous solution of an alkali metal hydroxide; the pH value of the electrolyte solution is 10-14. The voltage for selective oxidation of benzyl alcohol to assist hydrogen production via electrocatalysis is 1~2 V.